Prevalence of Hepatitis B and Hepatitis C Among Patients of Thalassemia Major at a Teaching Hospital in Larkana (Medical Forum Monthly, 2021)
Objective: To assess the frequency of Hepatitis B and Hepatitis C among patients of Thalassemia Major at a teaching hospital in Larkana.Study Design: Descriptive cross-sectional studyPlace and Duration of Study: This study was conducted at the conducted at Paediatric department, Shaheed Benazir Bhutto University Hospital, Larkana from June, 2017 to June, 2018.Materials and Methods: In the study total of 237 children with beta Thalassemia were selected by apply Non-probability consecutive technique sampling.Results: Prevalence of hepatitis B and C, was observed in 31(%) and 73(%) among thalassemia patients. More viral infections Hepatitis B and C seemed in the male in male than female and low socioeconomic population. Data were analyzed by using SPSS 19 version.Conclusion: Hepatitis B and C are quite more prevalent among Thalassaemic patients. It is significant, an alarming circumstance having a lot of aspects behind it, but it needs to be taken immediately. So a great need for proper screening of blood before transfusion to such patients and educational programs for these patients and their parents.